CD72 negatively regulates mouse mast cell functions and down-regulates the expression of KIT and FcεRIα. (19th September 2014) - Kataoka, Tatsuki R.; Kumanogoh, Atsushi; Fukuishi, Nobuyuki; Ueshima, Chiyuki; Hirata, Masahiro; Moriyoshi, Koki; Tsuruyama, Tatsuaki; Haga, Hironori
Abstract : CD72 downregulates both FcεRI and KIT via Cbl-b in mouse mast cells Abstract: CD72 is a transmembrane protein belonging to the C-type lectin family that is expressed by various hematopoietic cells. When bound to its natural ligand, CD100 (semaphorin 4D), CD72 inhibits the KIT-mediated responses of human mast cells, but not IgE/FcεRI-mediated mast cell degranulation. We extended these findings to examine the role of CD72 in mouse mast cells. CD72 expression was detected in mouse bone marrow-derived mast cells (mBMMCs). As for human mast cells, an agonistic antibody against CD72 (K10.6) suppressed the KIT-mediated cell growth of, IL-6 production by and chemotaxis of mBMMCs. However, in contrast to human mast cells, the IgE-triggered degranulation of mBMMCs was suppressed by K10.6. K10.6 did not affect the phosphorylation of SHP-1 in mBMMCs, although SHP-1 mediated the inhibitory effects of CD72 in human mast cells. Administration of K10.6 induced phosphorylation of the ubiquitin ligase Cbl-b and decreased the expression of KIT and FcεRIα on the surface of murine mast cells. We also observed expression of CD72 in a mouse neoplastic cell line, P815, harboring gain-of-function mutations in KIT genes. In addition, we found that K10.6 activated Cbl-b, down-regulated KIT expression and suppressed the mutated KIT-driven growth of these cells. Thus, the mechanism by which CD72 mediates inhibitory effects in mast cells is species-dependent.